2009
DOI: 10.1103/physrevlett.102.197002
|View full text |Cite|
|
Sign up to set email alerts
|

Pressure-Induced Superconducting State of Europium Metal at Low Temperatures

Abstract: Divalent Eu (4f;{7}, J=7/2) possesses a strong local magnetic moment which suppresses superconductivity. Under sufficient pressure it is anticipated that Eu will become trivalent (4f;{6}, J=0) and a weak Van Vleck paramagnet, thus opening the door for a possible superconducting state, in analogy with Am metal (5f;{6}, J=0) which superconducts at 0.79 K. We present ac susceptibility and electrical resistivity measurements on Eu metal for temperatures 1.5-297 K to pressures as high as 142 GPa. At approximately 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 26 publications
4
97
2
Order By: Relevance
“…The critical pressure at which Eu loses magnetic order is estimated to be 84 GPa, extrapolated from the data at 81 GPa and 82.5 GPa. It is significant that this pressure is the same as that (84 GPa) where superconductivity in Eu first appears at 1.8 K in magnetic susceptibility measurements; in the same study no superconductivity was observed above 1.4 K at 76 GPa [11]. While it is evident that pressure suppresses magnetism and induces superconductivity in Eu near 80 GPa, the precise phase boundaries remain to be accurately determined.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…The critical pressure at which Eu loses magnetic order is estimated to be 84 GPa, extrapolated from the data at 81 GPa and 82.5 GPa. It is significant that this pressure is the same as that (84 GPa) where superconductivity in Eu first appears at 1.8 K in magnetic susceptibility measurements; in the same study no superconductivity was observed above 1.4 K at 76 GPa [11]. While it is evident that pressure suppresses magnetism and induces superconductivity in Eu near 80 GPa, the precise phase boundaries remain to be accurately determined.…”
Section: Resultsmentioning
confidence: 71%
“…The high purity Eu sample (99.98% metal basis) is from the Materials Preparation Center of the Ames Laboratory [30], and from the same sample batch used in superconductivity studies in Ref. [11]. Due to its high reactivity, the sample was loaded into the diamond anvils cells in an Ar filled glove box together with 2-3 ruby spheres.…”
Section: Experimental Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Ce and Eu, both elements with unstable valences, have been demonstrated to become superconducting under pressure. The most recently discovered elemental superconductor, Eu, becomes superconducting above ∼80 GPa, 8 following a possible pressure-induced valence change from a strongly magnetic Eu 2+ (J = 7/2) configuration to weak Van Vleck paramagnetism in Eu 3+ (J = 0). Cerium metal undergoes an isostructural phase transition from the fcc γ-phase, characterized by Curie-Weiss local magnetic moment behavior, to the α-phase when subjected to a pressure of approximately 0.7 GPa at room temperature.…”
mentioning
confidence: 99%